INTEGRATED RISK MANAGEMENT MODELING IN THE PHARMACEUTICAL INDUSTRY X - Wahyudi, Hari
Pharmaceutical manufacturing, as a business organization faces some categories of risks that may affect the achievement of organizational goals. Such risks associated with the responsibilities of a pharmaceutical manufacturing in providing quality products that ensure the safety and efficacy of the consumer, in a sufficient amount and timely, competitive price basis, as well as all operations and the products have high levels of adherence to all regulations related to operations and products. Using of different models to manage each risk category causing their implementation is not pragmatic for the operationaLprocesses. At the time of the risk management implementation assessment, there are many difficulties to evaluate that risk management has adde& value to the achievement of organizational objectives and facilitate continuous improvement for the organization. This studies aims to create an integrated risk management model that can be applied to various categories of risks in the pharmaceutical manufacturing. The success of this studies measured by the ability of the model created to accommodate the various risk categories, identify potential risks associated with organizational objectives and identify improvement initiatives to facilitate continuous improvement. Studies carried out by developing the model, followed by the model testing to the three departments for four risk categories. The results of modeling are HWI 2016 Model, modeling for integrated risk management. The test results showed that the HWI 2016 Model able to accommodate four risk categories were tested, able to; identify the potential risks of 267.77% more, and able to bring 592% more improvement initiatives compared to existing models. The conclusion is HWI Model 2016 can be used as a integrated risk management model in the Pharmaceutical Industry X.